Peran Kepala Sekolah Dalam Pengelolaan Pembelajaran Guru Di SD Negeri 1 Pojok Tawangharjo Grobogan - Siswanto, Siswanto (2016)
Purpose of this study was to describe the characteristics of the administrative management of learning in primary schools 1 Pojok Tawangharjo Grobogan, to describe the characteristics of the management of learning activities in SD Negeri 1 Pojok Tawangharjo Grobogan, to describe the characteristics of the evaluation of the management of learning programs in SD Negeri 1 Pojok Tawangharjo Grobogan. Types of research used in this study is aqualitative approach to the design of ethnography. Research subjects at school heads, teachers, employees, students of SD Negeri 1 Pojok Tawangharjo Grobogan. Methods of data collection using interviews, observation, and documentation. Data analys is techniques to the analysis of the groove beginning of data collection, data reduction, data display, and verification / conclusions. Data validation was done by triangulation of methods and sources.The results of this study were 1) management of the learning administration can not be separated from the role of the principal, headmaster always perform administrative supervision of learning, field supervision of all administrative teachers have collected to be examined by the school principal; 2) the learning activities are passionate and spirit, the principal gave advice to teachers who do not perform management of learning activities and provide encouragement, school decision making involving all teachers, staff, and school committees including the princ ipal, learning activities supported by cooperation and coordination among teachers; 3) e valuation of the learning program is always held at this school programmatically and consistently, teachers play an important role in the evaluation of learning programs, teacher discipline can affect student success.